A Survey on Nanotechnology-Based Bioremediation of Wastewater - Lakshmi Thangavelu; Geetha Royapuram Veeraragavan (Bioinorganic Chemistry and Applications)
Rainwater discharge and human impacts produce wastewater, which is a contaminated type of water. Sediments also discharge phosphate into the water column when there is a lack of dissolved oxygen in the water. Through the manufacturing of environmentally benign nanoparticles, nanotechnology may reduce the amount of money spent by enterprises to remediate such contaminants. Because of their improved physiological, biochemical, and biomechanical qualities, nanoparticles are getting prominence. The importance of the global wastewater dilemma is discussed in this survey. The use of nanomaterials in heavy metal remediation (HMR) and wastewater treatment is covered in this survey. This paper also discusses the benefits of nanotechnology over traditional approaches in certain fields. This survey aims to gather together many recent studies on nanoparticle production and their benefits as adsorbents in the remediation of wastewater which have been done so far. The promising role of nanotechnology in wastewater remediation is surveyed in this research, which also discusses recent developments in nanotechnology-mediated remediation methods. This survey examines the vital potential of nanotechnology in wastewater treatment, as well as recent breakthroughs in nanotechnology-mediated treatment systems.